A novel anti-CD22 scFv–apoptin fusion protein induces apoptosis in malignant B-cells - Solmaz Agha Amiri; Soraya Shahhosseini; Najmeh Zarei; Dorsa Khorasanizadeh; Elahe Aminollahi; Faegheh Rezaie; Mehryar Zargari; Mohammad Azizi; Vahid Khalaj (AMB Express, 2017)
Abstract CD22 marker is a highly internalizing antigen which is located on the surface of B-cells and is being used as a promising target for treatment of B cell malignancies. Monoclonal antibodies targeting CD22 have been introduced and some are currently under investigation in clinical trials. Building on the success of antibody drug conjugates, we developed a fusion protein consisting of a novel anti-CD22 scFv and apoptin and tested binding and therapeutic effects in lymphoma cells. The recombinant protein was expressed in E. coli and successfully purified and refolded. In vitro binding analysis by immunofluorescence and flow cytometry demonstrated that the recombinant protein specifically binds to CD22 positive Raji cells but not to CD22 negative Jurkat cells. The cytotoxic properties of scFv–apoptin were assessed by an MTT assay and Annexin V/PI flow cytometry analysis and showed that the recombinant protein induced apoptosis preferentially in Raji cells with no detectable effects in Jurkat cells. Our findings indicated that the recombinant anti-CD22 scFv–apoptin fusion protein could successfully cross the cell membrane and induce apoptosis with high specificity, make it as a promising molecule for immunotherapy of B-cell malignancies.